Modelling in Accounting. Theoretical and Practical Dimensions - Teresa Szot-Gabryś (Contemporary Economics)
Accounting in the theoretical approach is a scientific discipline based on specific paradigms. In the practical aspect, accounting manifests itself through the introduction of a system for measurement of economic quantities which operates in a particular business entity. A characteristic of accounting is its flexibility and ability of adaptation to information needs of information recipients. One of the main currents in the development of accounting theory and practice is to cover by economic measurements areas which have not been hitherto covered by any accounting system (it applies, for example, to small businesses, agricultural farms, human capital), which requires the development of an appropriate theoretical and practical model. The article illustrates the issue of modelling in accounting based on the example of an accounting model developed for small businesses, i.e. economic entities which are not obliged by law to keep accounting records.